Penyusunan Laporan Keuangan Sesuai Sak EMKM Sebagai Pertanggungjawaban Pengelolaan Dana Desa pada Badan Usaha Milik Desa Surya Sejahtera Kedungturi Kecamatan Taman, Kabupaten Sidoarjo, Jawa Timur - Anita Amalia Firdaus Abdullah; Wiratna Wiratna (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to prepare the financial statements of the Surya Sejahtera Village-Owned Enterprise (BUMDes) to comply with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). BUMDes Surya Sejahtera, located in Kedungturi Village, Taman District, Sidoarjo Regency, manages an Integrated Waste Processing Facility (TPST) business unit. However, manual and unstandardized financial records result in incomplete and unsystematic financial statements, complicating strategic decision-making. This study used a qualitative descriptive approach, collecting data through interviews, documentation, and observation. The data obtained were analyzed to evaluate the compliance of the BUMDes' financial statements with the SAK EMKM principles. The results indicate that restructuring the financial statements in accordance with SAK EMKM resulted in more systematic, transparent, and accountable reports, consisting of a statement of financial position, an income statement, and notes to the financial statements. By preparing the financial statements in accordance with standards, the Surya Sejahtera BUMDes financial statements can improve transparency, accountability, and public and stakeholder trust in the management of village funds.